2020
DOI: 10.12740/pp/102438
|View full text |Cite
|
Sign up to set email alerts
|

The Staff Attitude to Coercion Scale (SACS) – Polish adaptation

Abstract: Cel pracyCelem badania było przygotowanie polskiej adaptacji kwestionariusza SACS. Skala ta jest narzędziem samooceny przeznaczonym do mierzenia stosunku pracowników do bezpośredniego przymusu wobec pacjentów oddziałów psychiatrycznych.MetodaPróba składała się z 120 pracowników 7 oddziałów psychiatrycznych. Kwestionariusz SACS to narzędzie stworzone w Norwegii przez Tonje Husum, składające się z 15 pozycji opisujących podejście pracowników psychiatrycznej służby zdrowia do bezpośredniego przymusu. Procedura wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…It has three subscales: a pragmatic attitude (Coercion as Care and Security), a critical attitude (Coercion as Offending), and a positive attitude (Coercion as Treatment), with sufficient reliability demonstrated for all three subscales (Cronbach's alpha 0.69–0.73) ( 21 ). Similar results have been found in other adaptations of SACS, including in Poland ( 29 , 31 ). The subscales are scored as the mean of the corresponding items ( 21 , 23 ).…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…It has three subscales: a pragmatic attitude (Coercion as Care and Security), a critical attitude (Coercion as Offending), and a positive attitude (Coercion as Treatment), with sufficient reliability demonstrated for all three subscales (Cronbach's alpha 0.69–0.73) ( 21 ). Similar results have been found in other adaptations of SACS, including in Poland ( 29 , 31 ). The subscales are scored as the mean of the corresponding items ( 21 , 23 ).…”
Section: Methodssupporting
confidence: 90%
“…In the first study on SACS in Poland, the same structure was found in factors related to so-called "pragmatic" attitudes (29). For many years, coercion was perceived as an integral part of Polish psychiatry.…”
Section: Factor Structure and Internal Consistency Of Factorsmentioning
confidence: 70%
See 2 more Smart Citations
“…The SACS was developed in 2008 (16); it has been used worldwide and translated into several languages (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). According to a systematic review performed by Husum et al (17), measurement properties of the SACS were reported in 13 studies conducted in Germany, Switzerland, Poland, the UK, the USA, India, Iran, Taiwan, and Norway, with six different language versions.…”
Section: Introductionmentioning
confidence: 99%